Inclusive Islamic Religious Education Curriculum Design in a Multicultural Society - Samsudin, Samsudin (Prodi PAI STIT Sunan Giri Bima, 2025)
This study is motivated by the reality of Indonesia's multicultural society and the challenges of Islamic Religious Education (PAI) in responding to the diversity of religions, cultures, and identities of students. The main purpose of this study is to analyze the design of an inclusive Islamic Education curriculum as a solution to these challenges. This research uses a qualitative approach with a type of library research. Data collection was conducted through the study of relevant documents related to PAI curriculum, multicultural education, and education policy. Data analysis used content analysis method to explore concepts and ideas related to inclusive PAI curriculum design. The results of this study identified four main points: (1) the urgency of inclusive PAI curriculum in accommodating the diversity of religion, culture, and identity of learners; (2) the principles of inclusive PAI curriculum design, including egalitarian, pluralistic, and empathic as a philosophical foundation; (3) the structure and content of inclusive PAI curriculum that includes core competencies, indicators, learning materials, and pedagogical approaches that are responsive to diversity; and (4) strategies for effective and sustainable implementation of inclusive curriculum in Islamic education institutions. This study concludes that the design of an inclusive Islamic Religious Education curriculum is an urgent need to create religious education that is relevant, fair, and able to build harmony in the world.